OPTIMIZING THE LIPID EXTRACTION PROCESS FROM ARTEMIA CYSTS. A COMPARATIVE ANALYSIS - Hajibayev, Quvvat Ganievich; Berdimbetova, Gulsara Esenovna; Nuriyeva, Mahbuba Urinbayevna; Asemenova, Nurjamol Yakupbaevna; Satimova, Mohira Rashidovna; Smetullaev, Mukhammedali Juginisovich (SCIENCE and SOCIETY, 2026)
Artemia (brine shrimp) cysts are the primary live-feed source in aquaculture for fish and crustacean larvae, and their nutritional value is largely determined by their lipid content and fatty-acid composition. The method used to extract lipids has a direct impact on the accuracy of scientific findings, yet different authors in the literature employ different extraction techniques (Folch, Bligh & Dyer, Soxhlet, sulfophosphovanillin), which complicates cross-study comparison. In this paper, the total lipid content and extraction methods reported in 11 scientific sources published between 1985 and 2019 (covering various geographic regions, strains, and developmental stages, totaling 47 data rows) were comparatively analyzed. The results showed that the Folch method is the most widely used and the most consistently reliable, functioning as a "gold standard," whereas the Bligh & Dyer method was found to fail to fully extract lipid from dried samples (yielding 30–45% lower results compared with Soxhlet cross-checks). On this basis, a step-by-step protocol is proposed for optimizing lipid extraction from Artemia cysts.